2001
DOI: 10.1063/1.1381049
|View full text |Cite
|
Sign up to set email alerts
|

Elastic properties of zinc tris(thiourea) sulphate single crystals

Abstract: Zinc tris(thiourea) sulphate (ZTS) single crystals possess excellent nonlinear optical properties and are nearly 1.2 times more efficient than potassium dihydrogen phosphate in optical harmonic generation. Large single crystals of this material have been grown from aqueous solution. All nine second order elastic stiffness constants of this orthorhombic crystal have been determined by measuring the velocity of propagation of ultrasonic waves of longitudinal and transverse polarizations along specific symmetry d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…The growth, vibrational studies and defect characterizations were reported in the literature [6,7]. The elastic property of ZTS was studied by ultrasonic waves interferometric techniques [8]. In the present paper the synthesis, growth aspects, linear and nonlinear optical properties, thermal and microhardness have been reported.…”
Section: Introductionmentioning
confidence: 96%
“…The growth, vibrational studies and defect characterizations were reported in the literature [6,7]. The elastic property of ZTS was studied by ultrasonic waves interferometric techniques [8]. In the present paper the synthesis, growth aspects, linear and nonlinear optical properties, thermal and microhardness have been reported.…”
Section: Introductionmentioning
confidence: 96%
“…The crystal density is 1850 kg/m 3 [2]. Under the conditions of growth applied the following walls were well [1,[7][8][9].…”
Section: Methodsmentioning
confidence: 99%
“…The crystal is particularly interesting because of its nonlinear optical properties. In the range 300 -350 K it does not show any anomalies in elastic properties [2]. In low temperatures the Raman spectroscopy data indicated anomalies at 60 K and 122 K, and the phase transition was characterised as a second order one [3].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The development of the theories of crystal growth has thrown more light on the understanding of crystal growth phenomena. Compared with inorganic NLO materials, organic materials may fulfill many of these requirements, but there are also some drawbacks with organic NLO materials such as environmental stability, poor chemical and mechanical stability, red-shift of the cut-off wavelength, low laser damage thresholds and poor phase matching properties [5][6][7][8][9][10][11][12]. In order to overcome these drawbacks and improve the properties, the growth of semi-organic crystals has nowadays come into prominence.…”
Section: Introductionmentioning
confidence: 99%